PREPARATION OF FINANCIAL STATEMENTS BASED ON SAK EMKM AT LAYANGAN BAYU SHOP - Meilisa Ariani; Yusuf Yusuf (Sean Institute, 2023)
The purpose of this study was to find out how the procedure for preparing financial statements based on SAK EMKM at the Bayu Kite Shop and to find out what factors hindered the preparation of these financial statements. This research method is qualitative. Data collection techniques were carried out through observation and interviews. The results of this study found that the Bayu Kite Shop did not have financial statements that were under SAK EMKM. The factors that hinder the preparation of financial statements are the owner does not understand the benefits of financial statements and the recording process is still considered difficult by shop owners.